Energy-Efficient UAV-to-User Scheduling to Maximize Throughput in Wireless Networks - Shakil Ahmed (IEEE Access, 2020)
The unmanned aerial vehicle (UAV) communication is a potential technology to meet the excessive next-generation cellular users' demand due to its reliable connectivity and cost-effective deployment. However, UAV communications have to be energy efficient so that it can save energy. Thus, the UAV flies sufficiently long enough time to serve the ground users with limited on-board energy. In this paper, we investigate an energy-efficient UAV communication via designing the UAV trajectory path. We consider throughput and the UAV propulsion energy consumption jointly. We assume that the UAV flies at a fixed altitude such that it can avoid tall obstacles. A binary decision variable is assigned to schedule UAV-to-user communication. First, we derive the UAV-to-user channel model based on the line of sight and non-line of sight communication links and jointly optimize the trajectory, transmit power, and the speed of UAV; and UAV-to-user scheduling to maximize throughput. Then, we apply the UAV propulsion energy consumption, which is a function of the UAV trajectory and speed. Finally, we formulate the UAV energy-efficiency maximization problem, which is defined as the total bits of information sent to the ground users by consuming the UAV energy for a given UAV flight duration. The formulated energy-efficiency maximization problem is non-convex, fractional, and mixed-integer non-linear programming in nature. We propose an efficient algorithm based on successive convex approximation and classical Dinkelbach method to achieve the optimal solution of energy-efficient UAV. We present simulation results to validate the efficacy of our proposed algorithms. The results show a significant performance improvement compared to the benchmark methods.